PENDIDIKAN LITERASI DIGITAL TENTANG HOAX DAN KONTEN NEGATIF DI MEDIA SOSIAL UNTUK REMAJA MASJID DI DESA KARYAMEKAR, GARUT - Patoni Patoni; Rizwan Martiadi; Ahmad Damiri; Subagiyo Subagiyo; Koko Adya Winata (JURNAL ABDIMAS PLJ, 2025)
Mosque youth in Karyamekar Village, Garut, are part of the younger generation who play a strategic role in building a healthy and moral social environment. The development of digital technology and social media has had a significant impact on the lives of adolescents, both positively and negatively. However, low digital literacy makes some adolescents susceptible to hoaxes and negative content on social media. This community service activity aims to improve the understanding and ability of mosque youth in recognizing, filtering, and responding wisely to hoaxes and negative content. The implementation method includes education, interactive discussions, and case study simulations. This training is effective in encouraging mosque youth in Karyamekar Village, Garut, to be more confident, have a clear direction for development, and be able to apply self-understanding in the learning process and social activities. It is hoped that this activity will shape mosque youth who are digitally savvy, critical, and responsible in using social media.